KEHUJJAHAN HADIS MENURUT IMAM MAZHAB EMPAT - Hamang, M. Nasri (DIKTUM: Jurnal Syariah dan Hukum, 2011)
This article presents the opinion of imams of four Islamic legal schools (mazhab) regarding the validity of hadits as the source of Islamic law. This study shows that the opinion of the imams on that issue is various. According to Abu Hanifah, al-sunnah can be accepted as the source of Islamic law with the condition that it is related by reliable men. As to hadits ahad, he requires that it does not contradict the principles agreed upon by ‘ulama, and its content (matan) does not concern with general issues, nor does it contravene the qiyas. He even accept the hadits mursal if it does not contradict the Quran. While according to Malik bin Anas, hadits can be accepted as the argumentation (hujjah), not only for hadits mutawatir, but also for hadits masyhur, hadits mursal, and hadits ahad, with the condition that they do not contradict the actions of Madinah scholars. Idris al-Syafi’i contends that hadits ahad can be accepted as the source of Islamic law with the requirement that it is related by dhabith transmitter. This is also the case with the hadits mursal. According to Syafi’i, the status of hadits mutawatir is higher than hadits ahad and hadits mursal. Another imam, Ahmad bin Hanbal, uses all kinds of hadits, mutawatir, ahad, mursal, and dha’if, as the sources of Islamic law. He even prefers hadits dha’if